Population Pharmacokinetics of Tranexamic Acid in Chinese Population Undergoing Cardiac Surgery with Cardiopulmonary Bypass - Liu Y; Zhou C; Lv H; Tian L; Jiang J; Shi J (Drug Design, Development and Therapy, 2025)
Yue Liu,1 Chenghui Zhou,2 Hong Lv,1 Lei Tian,3 Juanjuan Jiang,3 Jia Shi1 1Department of Anesthesiology, State Key Laboratory of Cardiovascular Disease, Fuwai Hospital, National Center for Cardiovascular Diseases, Chinese Academy of Medical Sciences and Peking Union Medical College, Beijing, People’s Republic of China; 2Center for Anesthesiology, Beijing Anzhen Hospital, Capital Medical University, Beijing, People’s Republic of China; 3NHC Key Laboratory of Clinical Research for Cardiovascular Medications, National Clinical Research Center of Cardiovascular Diseases, Fuwai Hospital, Chinese Academy of Medical Sciences and Peking Union Medical College, Beijing, People’s Republic of ChinaCorrespondence: Jia Shi, Email shijia@fuwai.comBackground: Population pharmacokinetics (PK) models could provide specific references for the formulation of personal drug delivery protocols, however, there is no population PK study of tranexamic acid (TXA) have been conducted in the Chinese population. The aim of this study was to establish a population PK model based on the data of perioperative plasma concentrations in Chinese participants, and to provide a reference for individualized administration of TXA.Methods: Participants undergoing cardiac surgery were randomly assigned to high-dose of TXA group (a 30-mg/kg bolus, a 16-mg/kg/h maintenance dose, and a 2-mg/kg prime, n = 7) and low-dose group of TXA (a 10-mg/kg bolus, a 2-mg/kg/h maintenance dose, and a 1-mg/kg prime, n = 9). Blood samples were collected at 14 time points and the concentration of TXA was determined by liquid chromatography-tandem mass spectrometry. Modelling was performed using Phoenix NLME 8.3 software.Results: The primary covariate identified was body weight, while no significant influence of cardiopulmonary bypass (CPB) on the PK was detected. The population estimates for clearance (CL1), volume of the central compartment (V1), diffusional clearance (CL2), and volume of peripheral compartment (V2) were 4.7 L/h, 4.9 L, 17.0 L/h, and 11.1 L, respectively, assuming a bodyweight of 70 kg.Conclusion: This study provides the first population PK model of TXA in the Chinese population undergoing cardiac surgery with CPB. The model could serve as a reference for the future development of individualized TXA administration strategies, with target-controlled infusion (TCI) emerging as a viable option.Plain Language Summary: What is already known on this topic?Tranexamic acid is an antifibrinolytic drug that has been demonstrated to reduce the requirement for allogeneic blood transfusions in cardiac surgery with CPB. However, prolonged or high-dose sustained tranexamic acid transfusions have been associated with an increased risk of seizures.What this study adds?This study presents the population pharmacokinetics of tranexamic acid in a Chinese population undergoing cardiac surgery with cardiopulmonary bypass, and develops the first population pharmacokinetic model for the Chinese population.How this study might affect research, practice or policy?The model will facilitate the future promotion of individualized dosing of tranexamic acid, ensuring adequate antifibrinolytic effects while reducing adverse effects. Target-controlled infusion based on population modelling is a potential avenue for further consideration.Keywords: tranexamic acid, population pharmacokinetics, blood conservation, cardiac surgery, cardiopulmonary bypass